Longitudinal stability of progression-related microglial activity during teriflunomide treatment in patients with multiple sclerosis - Lehto Jussi; Nylund Marjo; Matilainen Markus; Sucksdorff Marcus; Vuorimaa Anna; Rajander Johan; Wahlroos Saara; Hariri Parisa; Laura Airas (WILEY, 2025)
Background and purpose: The aim was to study brain innate immune cell activation in teriflunomide-treated patients with relapsing-remitting multiple sclerosis.
Methods: Imaging with 18-kDa translocator protein positron emission tomography (TSPO-PET) using the [C-11]PK11195 radioligand was employed to assess microglial activity in the white matter, thalamus and areas surrounding chronic white matter lesions in 12 patients with relapsing-remitting multiple sclerosis who had been treated with teriflunomide for at least 6 months before inclusion. Magnetic resonance imaging (MRI) was used to measure lesion load and brain volume, and quantitative susceptibility mapping (QSM) was used to detect iron rim lesions. These evaluations were repeated after 1 year of inclusion. Twelve age- and gender-matched healthy control subjects were imaged for comparison.
Results: Half of the patients had iron rim lesions. In TSPO-PET, the proportion of active voxels indicating innate immune cell activation was slightly greater amongst patients compared with healthy individuals (7.7% vs. 5.4%, p = 0.033). The mean distribution volume ratio of [C-11]PK11195 was not significantly different in the normal-appearing white matter or thalamus amongst patients versus controls. Amongst the treated patients, no significant alteration was observed in positron emission tomography distribution volume ratio, the proportion of active voxels, the number of iron-rim-positive lesions, lesion load or brain volume during follow-up.
Conclusions: Compared to controls, treated patients exhibited modest signs of diffuse innate immune cell activity, which was unaltered during follow-up. Lesion-associated smoldering inflammation was negligible at both timepoints. To our knowledge, this is the first study applying both TSPO-PET and QSM-MRI to longitudinally evaluate smoldering inflammation.